THE NEED FOR INFORMATION AND COMMUNICATION TECHNOLOGIES IN AGRICULTURE - Allaniyazov Parakhat Ataniyazovich; Ataniyazova Zukhra Parakhatovna (Scholar Express Journals, 2025)
The article examines the use and development of information technologies (hereinafter referred to as IT) in agriculture in Uzbekistan. Agriculture is a long and complex business, requiring large financial investments.
Keywords: Information technology; agribusiness; technology